NUMERICAL MODELING OF VENTURI FLOWS FOR DETERMINING AIR INJECTION RATES USING FLUENT V6.2 - Baylar, Ahmet; Aydin, M. Cihan; Unsal, Mehmet; Ozkan, Fahri (Assoc Sci Res, 2009)
As the water passes through a restriction in a pipe, it forms a vacuum at the end of the restriction. A hole bored into the pipe at a point where this vacuum occurs will cause air to be drawn into the main flow. One example of this mechanism is seen in the Venturi tube. When a minimal amount of differential pressure exists between the inlet and outlet sides of the Venturi tube, a vacuum occurs at suction holes of the Venturi tube. Venturi aeration is a method of aeration that has become popular in recent years. In present paper, air injection rates of Venturi tubes are analyzed using Computational Fluid Dynamics modeling. These analyses are carried out by means of the program FLUENT V6.2 that uses finite volume theory. There is a good agreement between the measured air injection rates and the values computed from FLUENT CFD program.
Keywords: Aeration; Air injection; Computational Fluid Dynamics; Venturi